Activity-dependent spinal cord neuromodulation rapidly restores trunk and leg motor functions after complete paralysis. - Rowald, Andreas; Komi, Salif; Demesmaeker, Robin; Baaklini, Edeny; Hernandez-Charpak, Sergio Daniel; Paoles, Edoardo; Montanaro, Hazael; Cassara, Antonino; Becce, Fabio; Lloyd, Bryn; Newton, Taylor; Ravier, Jimmy; et al. (Nature Medicine, 2022)
Epidural electrical stimulation (EES) targeting the dorsal roots of lumbosacral segments restores walking in people with spinal cord injury (SCI). However, EES is delivered with multielectrode paddle leads that were originally designed to target the dorsal column of the spinal cord. Here, we hypothesized that an arrangement of electrodes targeting the ensemble of dorsal roots involved in leg and trunk movements would result in superior efficacy, restoring more diverse motor activities after the most severe SCI. To test this hypothesis, we established a computational framework that informed the optimal arrangement of electrodes on a new paddle lead and guided its neurosurgical positioning. We also developed software supporting the rapid configuration of activity-specific stimulation programs that reproduced the natural activation of motor neurons underlying each activity. We tested these neurotechnologies in three individuals with complete sensorimotor paralysis as part of an ongoing clinical trial ( www.clinicaltrials.gov identifier NCT02936453). Within a single day, activity-specific stimulation programs enabled these three individuals to stand, walk, cycle, swim and control trunk movements. Neurorehabilitation mediated sufficient improvement to restore these activities in community settings, opening a realistic path to support everyday mobility with EES in people with SCI.
EVALuna2:562143